Planejamento baseado em capacidades como potencializador da interoperabilidade: as experiências australiana e canadense transformadas em insumos para o caso do Brasil - Freire, Maria Eduarda Laryssa Silva (2021)
The post-Cold War scenario was an important catalyst in the search for changes in the way military affairs and operations were conducted, given that the threat to States was no longer focused specifically on a country to be something more diffuse, difficult to identify, as the challenges presented by transnational crime and terrorism. Through Defense Transformation greater attention was given to joint military operations in order to advocate integration between the different branches of the Armed Forces. In this context, there is a tendency of change regarding the adopted defense planning model. It used to plan focusing on a particular threat, however, more and more countries have opted for the adoption of Capabilities-Based Planning (CBP), a methodology that, among its characteristics, promotes greater interoperability (systems, units or forces capable of exchanging services and/or information). The objective of this research is to understand how this joint planning methodology contributes to improve interoperability, based on the analysis of experiences in Australia and Canada, with the aim to provide inputs for thinking about the case of Brazil. The development of the study was based on the hypothesis that this improvement takes place through the intensification of organizational integration, which occurs through the deepening of joint structures, provided by the instruments of the joint systematics. The progress of the investigation was guided by a methodological strategy, structured from the Comparative Study method and the tools of cross case analysis, the study of few cases (small-n) and the Most Similar System Design. From the study of the experiences of Australia and Canada, it was possible to conclude that the CPB promotes a joint perspective that influences the entire defense structure, from the ministerial level to the service level. Adopting a top-down approach, standardizing the taxonomy of the process, creating permanent joint commands, and military capabilities being jointly planned and developed are some of the contributions of the CBP to the interoperability and jointness process. These results allowed to conclude that Brazil, a country in the initial phase of its implementation of the CBP, can incorporate many of the lessons bequeathed by these countries, in order to develop a process that is less affected by the rigid structures of defense.